Utilization of Tofu Liquid Waste to Extend the Freshness Life and Reduce Escherichia Coli Contamination in Tofu - Sudaryantiningsih, Cicik; Pambudi, Yonathan Suryo (Formosa Journal of Applied Sciences, 2024)
This research aims to: 1) Describe the potential of LCT in extending the shelf life of tofu, 2) Analyze the potential of LCT in reducing Escherichia coli contamination in tofu, and 3) Compare the taste, smell and texture of tofu soaked in LCT with control tofu. This research is conducted in two steps. The first stage involved observing the color, smell, and texture of tofu soaked in LCT with concentrations of 25%, 50%, 75%, and a control soaked in pure water. The second stage involved observing E. coli contamination in tofu soaked in various solutions and also control tofu. The conclusions of this research are: 1) Tofu soaked in pure water for more than 2 days shows Escherichia coli contamination which makes tofu unfit for consumption, 2) Soaking tofu in 75% LCT can extend the freshness of tofu by up to 4 days and reduce bacterial contamination E.